Molecular analysis of the UROD gene in 17 Argentinean patients with familial porphyria cutanea tarda: Characterization of four novel mutations - Mendez, Manuel (2012)
Porphyria cutanea tarda (PCT) is caused by decreased activity of uroporphyrinogen decarboxylase (UROD) in the liver. The disease usually occurs in adulthood and is characterized by cutaneous photosensitivity, hyperpigmentation, skin fragility and hypertrichosis, due to the accumulation of porphyrins produced by oxidation of uroporphyrinogen and other highly carboxylated porphyrinogens overproduced as a result of the enzyme deficiency. PCT is generally sporadic, but about 20-30% of patients have familial-PCT (F-PCT) which is associated with heterozygosity of mutations in the UROD gene. In the present study we have found the molecular defect in seventeen unrelated Argentinean patients with F-PCT, identifying a total of eleven UROD gene mutations: four novel and seven previously described. The novel mutations were: a guanine insertion at the 5´ splice junction of intron 2, a three nucleotide deletion causing the lost of valine 90, a deletion of 22 bp in exon 6 and a deletion of part of the polyadenylation signal. Prokaryotic expression studies showed that the novel amino acid deletion resulted in an inactive protein. Mutations c.10insA and p.M165R, previously found in Argentinean patients, were recurrent in this study; they are the most frequent in Argentina accounting for 40% of the mutant alleles characterized to date.